Molecular docking of combretastatin derivatives to combat human cancer cells - Kshitij Chitnis; Jasdev Singh Tuteja; Priti Patidar (Journal of the Scientific Society, 2024)
Cancer is defined as the group of diseases which involve abnormal cell growth or controlled growth of abnormal cells that are present in any part of the body. The causative agents of cancer are chemical, environmental, viral, and mutagenic, which lead to the mutation of genes into oncogenes, which provoke or demean regulatory biochemicals, resulting in accelerated cellular growth. Combretastatin was selected as the candidate because it is a water-soluble prodrug which is quickly converted into combretastatin A4, a cancer-fighting substance. It has longer circulation, better drug targeting, increased efficiency, and fewer side effects. The research was carried out to find a potential drug that could inhibit the action of cancer in humans. In the experiment, 21 derivatives of combretastatin were subjected to molecular docking for analyzing the binding interactions of the derivative with the active site using the Protein Data Bank: 3DK9 through Molegro Virtual Docker 6.0. The docking showed that the (E)-1-(2,6-dimethoxypyridin-4-yl)-3-(1H-indol-3-yl)-2-methylprop-2-en-1-one was the most potent, had a Mol Dock score of-194.925 and gave interactions with Asp331, Gly31, and Thr57. Thus, this research can be further extended further to have more potent drugs.